Diagnostic Value of Cone-Beam Computed Tomography and Periapical Radiography In Detection of Vertical Root Fracture - Ezzodini Ardakani, Fatemeh; Razavi, Seyyed Hossein; Tabrizizadeh, Mahdi (Iranian Endodontic Journal, 2015)
Introduction: Vertical root fracture (VRF) is the longitudinal fracture of the root in endodontically treated teeth. Considering the limitations of two-dimensional radiographic images in detection of VRF and introduction of cone-beam computed tomography (CBCT), this study was designed to find the sensitivity, specificity and accuracy of CBCT and periapical (PA) radiography in detection of VRFs. Methods and Materials: This was a cross-sectional in vitro study on 80 extracted human single canal teeth including 40 maxillary and 40 mandibular teeth. After standardized endodontic treatment of the roots, VRF was induced in half of the teeth in each group, and other half were left without fracture. Teeth were inserted in dry maxillary and mandibular alveoli. PA radiographs and CBCT images were taken from the specimens. Data were analyzed with SPSS software. The McNemar test was used to evaluate the sensitivity, specificity and accuracy of images, and kappa coefficient was used to assess the degree of agreement between the observers. The level of significance was set at 0.05. Results: Sensitivity and specificity values of CBCT were 97.5% and 95%, respectively. However, for PA radiography the sensitivity and specificity were 67.5% and 92.5%, in order of appearance. Accuracy of CBCT (96.25%) and PA radiography (80%) in both jaws were significantly different (P=0.022). Two methods were not significantly different when testing specificity (P=0.298). Conclusion: This study showed that the sensitivity and accuracy of CBCT in detection of vertical root fracture are higher than periapical radiography. CBCT can be recommended to be used in detection of vertical root fractures.